2011
DOI: 10.3109/0142159x.2010.530703
|View full text |Cite
|
Sign up to set email alerts
|

Student perspectives on patient educators as facilitators of interprofessional education

Abstract: Results suggest that trained patient educators can effectively facilitate interprofessional interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 4 publications
1
24
0
11
Order By: Relevance
“…Medical students scored lower on readiness for IPE than nursing students, but higher on the perceived need for collaboration and the actual collaboration [31]. The use of simulation or standardized patients in IPE had a positive effect on readiness for IPE [32]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Medical students scored lower on readiness for IPE than nursing students, but higher on the perceived need for collaboration and the actual collaboration [31]. The use of simulation or standardized patients in IPE had a positive effect on readiness for IPE [32]. …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies applied a combination of two or more questionnaires. [30, 32, 40, 47, 49, 58, 61, 65] A post-intervention interview, focus group or writing assignment offers the student an opportunity to reflect on the interprofessional experience, as was done in 16 studies. [25, 27, 32, 34, 37, 4345, 51, 5355, 65, 69, 71, 72] More than 15 different instruments or their adaptations were applied in the 65 studies in this review (see Additional file 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A few studies have revealed the value of allowing patient‐instructors to share their stories of how disease and illness have affected their lives. For example, a qualitative study conducted by Solomon found that the most engaging or helpful learning moment, identified from student responses to a questionnaire about being taught by a patient‐educator, was that spent hearing the patient's personal story and experience . Vail et al .…”
Section: Introductionmentioning
confidence: 99%